La aplicación de una ley interpretativa a la nueva tabla del CONSEP considerándola como un derecho constitucional por ser un problema de salud pública y el micrográfico en el Ecuador - Aldas Pincay, Isaac Sebastián (2016)
This work prior to obtaining a law degree to which we have entitled called "The regulation of an interpretative law to the new table of Consep considering it as a constitutional right to be a public health problem and microtrafficking in Ecuador investigation. "it is aimed to investigate and bring to an intermediate view to modifying the table of maximum possession of narcotics and psychotropic substances of 2015, seeking to identify the level of tolerance of patients with additions and avoid prison instead of attention as a problem of public health and this postulate we have become general objective pro be the reason that led us to choose a topic of delicadez sum and more human than that of a punitive nature, the impact it has had on society character and in the family, addictions…….